2007
DOI: 10.12693/aphyspola.112.363
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Co-Doped ZnO Bulk Crystals

Abstract: Low-temperature Raman spectra of a bulk mixed crystal Zn 1−x Co x O (x = 0.016) are shown and analyzed. Besides the common modes of the ZnO host lattice, electronic transitions related to the presence of Co 2+ ions at the Zn sites are observed. In spite of the low Co concentration the presence of collective excitations corresponding to Co and CoO precipitates is also revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…As it has been demonstrated previously by Raman scattering measurements performed in a much wider spectral range [17], the investigated sample contains both Co and CoO precipitates. None of these secondary phases exhibit any vibration, electronic, or magnetic excitations that may be the origin of the observed Raman signal at the frequency given above.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…As it has been demonstrated previously by Raman scattering measurements performed in a much wider spectral range [17], the investigated sample contains both Co and CoO precipitates. None of these secondary phases exhibit any vibration, electronic, or magnetic excitations that may be the origin of the observed Raman signal at the frequency given above.…”
Section: Resultsmentioning
confidence: 63%
“…The bulk sample containing approximately 1.6 at.% of Co [17] has been selected for a further analysis with the use of the Raman spectroscopy. The total Co content in the investigated sample was determined by two independent methods: by the electron microprobe and by measurements of magnetic properties (from the saturation of magnetization).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…have found that CoO‐related magnon peaks in the Co‐added ZnO crystal system. Szuszkiewicz et al . identified the LVM and CoO‐related magnons modes at low‐temperature regime.…”
Section: Resultsmentioning
confidence: 99%
“…The coexistence of CoO and ZnO phases were identified through low‐temperature Raman spectra by Millot et al . Szuszkiewicz et al . also observed the Co‐related local vibrational modes (LVM) in Co‐doped ZnO bulk crystals by Raman spectral measurements.…”
Section: Introductionmentioning
confidence: 99%